A Case Study on the Influence of Palatal Conditions on Language Ability in Early Childhood - Nurul Shifa Fauziah; Brigita Puridawaty; Mahzura Mahzura; Anni Farhani; Vuspa Nurvaera; Musoheh Musoheh (Kirana Publisher (KNPub), 2026)
This case study examines language development in a five-year-old child with a palatal physical abnormality, focusing on differences among receptive language, early literacy skills, and expressive language. Observational findings indicate that the child’s receptive language development is age-appropriate, as shown by the ability to understand instructions, recognize vocabulary, and participate effectively in conversations. In addition, early literacy skills are well developed, reflected in the ability to recognize letters, associate sounds with symbols, and comprehend simple stories. However, the most significant area of difficulty is expressive language. This is characterized by limited vocabulary, short sentence production, difficulties in articulating certain speech sounds, and the presence of hypernasality. Although the child has undergone palatal surgery, speech function has not fully recovered, resulting in expressive language abilities that remain below age expectations. These expressive language difficulties are influenced by limitations in articulatory function, suboptimal control of airflow, restricted communication experiences, and the possibility of mild hearing impairment.